Key challenges of the development of the Belarusian State in the focus of media and the level of social tension: sociological reconstruction - Belski, Alexander M. (Journal of the Belarusian State University. Sociology, 2019)
The article defines the essence and provides a methodology for calculating the indicator of the level of social tension as an objective state of society. Its interrelation with processes in economic, political and social spheres is reflected with its specificity. The adequacy of the index is demonstrated with the help of content analysis of the mass media with subsequent sociological reconstruction of the events of the socio-political life of the country. The factors of possible destabilization of the country’s sustainable development are presented. Their classification is given for several reasons. The conclusion is drawn about the complex influence of the factors, as well as the necessity of their interrelation. The main emphasis is on the effect of the economic factor. The article contains actual examples of the indicated contradictions of the Belarusian reality, supported by the results of sociological research. The recommendation is made to continuously take into account the dynamics of the indicator of the level of social tension in the process of making managerial decisions.
Keywords: sustainable development; the state; social tension; factors; destructive factors; social and economic development